How the home learning environment contributes to children’s social–emotional competence: A moderated mediation model - Li, Shaomei; Tang, Yu; Zheng, Yuxin (Frontiers in Psychology, 2023)
The home learning environment is the earliest contact learning environment in early childhood development, which plays an important role in the development of children’s social-emotional competence. However, previous studies have not clarified the precise mechanisms by which the home learning environment influences children’s social-emotional competence. Therefore, the study selected a sample of 443 children from 14 kindergartens in western China and explored the relationship between the home learning environment and its intrinsic structure (i.e. structural family characteristics, parental beliefs and interests, and the educational processes) and children’s social-emotional competence. The results of the study reported that (1) structural family characteristics and parental beliefs and interests both had a significant positive predictive effect on children’s social-emotional competence. (2) the educational processes fully mediate between structural family characteristics, parental beliefs and interests, and children’s social-emotional competence. (3) gender moderated the effect of the home learning environment on children’s social-emotional competence. Gender moderates not only the indirect effects between parental beliefs and interests and children’s social-emotional competence, but also the indirect effects between structural family characteristics and children’s social-emotional competence. At the same time, gender also moderated the direct effects between parental beliefs and interests and children’s social-emotional competence. The results emphasize the crucial role of the home learning environment in the development of children’s early social-emotional competence. Therefore, parents should pay attention to the home learning environment and improve their ability to create a home learning environment that promotes the positive development of children’s social-emotional competence.